Malarial pigment-induced lipoperoxidation, inhibited motility and decreased CCR2 and TNFR1/2 expression on human monocytes - Oleksii Skorokhod; Valentina Barrera; Elena Valente; Daniela Ulliers; Koji Uchida; Evelin Schwarzer (Redox Experimental Medicine)
Objective: Malaria remains an important life-threatening disease that provokes a complex immune response, marked by an initial immune boost followed by long-term suppression, warranting further study. One of the manifestations of compromised immune response is co-infections, which are frequently reported in malaria patients and post-malaria convalescent individuals. Monocyte motility is a crucial step in immune cell recruitment, but this process is not fully efficient in malaria. Malarial pigment hemozoin, avidly phagocytosed by monocytes, inhibits important monocyte functions through lipoperoxidation. Methods: 4-Hydroxynonenal (4-HNE) adducts were detected on primary human monocytes by fluorescent microscopy, and CCR2 and TNFR1/2 receptors by flow cytometry. A two-dimensional migration microfluidic assay was applied for studying monocyte motility. Results: We show here that, following hemozoin ingestion, monocyte motility is inhibited. This is accompanied by a 2.4 ± 0.3-fold increase of the adducts of the lipoperoxidation product 4-HNE with monocyte proteins. Reduction of cell directional motility by 3.2 ± 0.6 times in response to MCP-1 and by 3.8 ± 1.1 times in response to TNF-α is observed alongside a decrease in CCR2 expression by 55 ± 8%, TNFR1 (CD120a) expression by 79 ± 4% and TNFR2 (CD120b) expression by 58 ± 7%. Conclusions: The low availability and potential malfunction of these important chemotactic receptors could be proposed as an additional mechanism for the poor immune response in malaria. Therapeutic relevance could be found in interventions aimed at regulating damaged or downregulated receptors and the application of antioxidants or other reagents to contrast protein addition of free 4-HNE. Significance statement: The study deepened our knowledge about lipid peroxidation processes, which are related to infectious diseases and immunity. Observed impaired immune motility and collapse of receptors could explain immunosuppression manifestations and co-infections in malaria and other diseases accompanied by oxidative stress.